Ice age - Berg, Michael; Wilson, Michael J.; Ackerman, Peter; Romano, Ray.; Leguizamo, John.; Leary, Denis; Visnjic, Goran, 1972-; Black, Jack, 1969-; Cedric, the Entertainer, 1965-; Root, Stephen; Bader, Diedrich, 1966-; Twentieth Century-Fox Film Corporation; et al. (Beverly Hills, Calif. 20th Century Fox Home Entertainment, 2002)
Twenty thousand years ago, as the Earth was being overrun with glaciers, Manny, Diego, Sid and Scrat become a courageous quartet of migrating misfits braving the frozen terrain and embarking on an incredible journey. Creatures everywhere were fleeing the onslaught of the new Ice age ...
DVD.
Rated PG.
Title from disc.
Features include: Disc 1. full-length audio commentary by dirtector Chris Wedge and co-director Carlos Saldanha ; 3 new interactive games ; 8 DVD-ROM games/activities -- Disc 2. Scrat's missing adventure ; "Behind the scenes of Ice Age." HBO special ; 6 deleted scenes in English French & Spanish (with optional director's commentary) ; 6 production featurettes ; The making of Ice Age documentary ; scene-specific commentary by John Laguizamo as Sid ; 3 interactive animation studies ; international (multi-language) clip ; Scrat's mini promo spots ; Blue Sky Studios' Oscar winning animated film: "Bunny" (with optional director's commentary) ; Ice Age theatrical teaser, trailers & more.
English 5.1 Dolby surround ; French and Spanish Dolby surround.
Animators, Nina Bafaro ... [et al.] ; editor, John Carnochan ; music, David Newman ; production designer, Brian McEntee.
Keywords: Glacial epoch -- Drama; Woolly mammoth -- Drama; Saber-toothed tigers -- Drama; Friendship -- Drama; Feature films